Pickleball Assessment of Skill and Tactics. (3rd March 2020) - Michael, Robert; Webster, Collin
Abstract : The purpose of this article is to introduce the Pickleball Assessment of Skill and Tactics (PAST). The development of the PAST was to address the grade-level outcomes for middle school physical education and provide empirical evidence that physical education teachers can use as formative and/or summative assessment data to guide instruction and chart student progress toward meeting the grade-level outcomes. The PAST combines skill execution and tactical decisions by measuring student success rate through an event recording observation system. The instrument focuses on the execution of the serve and ground strokes, as well as the tactical decisions of returning to a recovery position and the ability to use shot selection to move opponents' side-to-side or front-to-back. Implementation of the instrument is designed to be used by teachers or by students as a peer assessment that can be used during modified game play or with videotaped gameplay.